Efektivitas Video Pembelajaran Peduli Stunting Terhadap Tingkat Pengetahuan dan Keterampilan pada Kader Kesehatan - Masmuri; Nurul Hidayah; Dodik Limansyah (Institut Citra Internasional, 2025)
The incidence of stunting can be influenced by several factors, namely low levels of knowledge and inadequate attitudes or practices regarding the care of children with stunting. Health cadres must acquire basic information technology-based skills to help people obtain health care. This research aims to examine the effectiveness of the